The Influence of Marketing Strategy and Entrepreneurial Competence on Competitive Advantage and its Implications for Marketing Performance (A Survey on Fashion, Culinary and Craft Small and Medium Industries Assisted By The Department of Trade And Industry of Bandung City) - Maulida, Dewi; Febrian, Febry; Mulyana, Agus (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this study was to determine and analyze: (1) To find out the marketing strategy in small and medium industries according to respondents, (2) To find out about entrepreneurial competence towards small and medium industries, (3) To determine competitive advantage in small and medium industries, (4 ) To determine marketing performance in small and medium industries, (5) To determine the effect of marketing strategy and entrepreneurial competence on competitive advantage, (6) To determine the effect of competitive advantage on marketing performance, either simultaneously or partial. The research method used in this research is descriptive and verification, the unit of analysis in this study is the small and medium industrial business actors assisted by the Department of Trade and Industry of Bandung City as many as 80 people. Based on the results of the study, it was found that: The marketing strategy in the small and medium industry of fashion, culinary and craft assisted by the Department of Trade and Industry of the City of Bandung was classified as very good, especially in terms of media promotion (online/offline), entrepreneurial competence in the small and medium industry of fashion, culinary and craft assisted by the Department of Trade and Industry of the City of Bandung is classified as very good, especially in terms of commitment competence, Competitive advantage in the small and medium industry of fashion, culinary and craft assisted by the Department of Trade and Industry of the City of Bandung is classified as very good, especially in terms of maintaining product quality, Marketing performance at Small and medium industries of fashion, culinary and craft assisted by the Department of Trade and Industry of the City of Bandung are classified as very good, especially in terms of quality, both simultaneously and partially marketing strategies and entrepreneurial competencies have a significant effect on competitive advantage in the industry. i small and medium fashion, culinary and craft assisted by the Department of Trade and Industry of the City of Bandung, competitive advantage has a significant effect on marketing performance in the small and medium industry of fashion, culinary and craft assisted by the Department of Trade and Industry of the City of Bandung,